The origin, nature and distribution of gypsum crusts in deserts - Watson, A; Watson, A. (1983)
﻿ All the warm deserts of the world exhibit gypsum crusts in favourable localities, generally areas with a source of gypsum and less than 250 mm of rainfall annually. The features, comprising loose powdery or cemented crystalline accumulations of calcium sulphate dihydrate, are found at the surface or within the uppermost 10 m of regolith. Thicknesses vary from a few millimetres to several metres and purities range from about 15% to nearly 100% gypsum. A review of the literature on gypsum soils and crusts reveals that the classification of types requires both standardizing and simplifying. A preliminary classification of crusts into three types can be made on the basis of structural and stratigraphic characteristics of examples from southern Tunisia and the Central Namib Desert. The types consist of subaerial aqueous evaporites, two subsurface and three surface forms. Detailed physical and chemical analyses justify a broadly similar genetic classification though one subsurface form is believed to be a primary pedogenic type of which the surface forms represent relics at various stages of solutional deterioration. Examples of subaerial aqueous evaporites are all products of shallow-water sedimentation in seasonally flooded chotts and sabkhas. The non-pedogenic subsurface type, croûte de nappe, is produced by displacive crystallization at the surface of a fluctuating water table. Gypsum precipitation results from either evaporation or mixing of saline waters causing saturation with respect to gypsum. Surface gypsum crusts are subsurface illuvial accretions exposed by erosion of overlying material. The gypsum is derived from solution of surface aeolian, atmospheric, colluvial or alluvial deposits by meteoric waters which percolate into the upper soil zone replenishing the antecedent soil moisture deficit. Subsurface accumulation results from displacive crystallization at host sediment grain contacts when gypsum saturated soil moisture evaporates.